Effects of sodium bicarbonate therapy on cognitive and cerebrovascular function in midlife and older adults with chronic kidney disease: a pilot randomized trial - Fangning Gu; Zhiying You; Nell Hawkins; Rachael Reddin; Rahaf Hamour; Allison Shapiro; Christina Coughlan; Douglas Seals; Seth Furgeson; Angelina Dixon; Kristen L. Nowak; Jessica Kendrick (BMC Nephrology)
Abstract Introduction Metabolic acidosis may create a pathway to cognitive impairment in chronic kidney disease (CKD) by contributing to cerebrovascular dysfunction. Trials examining the effect of sodium bicarbonate (NaHCO3) on cognitive function are lacking. Methods We conducted a randomized, double-blind, placebo-controlled pilot study examining the effect of 12 months of NaHCO3 on cognitive function in 34 patients aged 50–80 years with CKD stage 3b-4 (eGFR 15–44 ml/min/1.73m2) with metabolic acidosis (serum bicarbonate level 16–22 mEq/L). Participants were randomized 1:1 to NaHCO3 or placebo. The primary endpoint was change in overall cognition (Cognitive Function Composite score) assessed by the NIH Toolbox® Cognition Battery over 12 months. Secondary endpoints were change in cerebrovascular reactivity and pulsatility of the middle cerebral artery (MCA) assessed by Transcranial Doppler Ultrasonography over 12 months. Results 33 patients completed the study. After 12 months of treatment with NaHCO3 therapy, the Cognitive Function Composite score increased significantly from baseline (mean ± SD, 47.3 ± 8.5 to 49.3 ± 11.0, p = 0.03), however, there was no difference compared to placebo (p = 0.39). NaHCO3 therapy resulted in a significant reduction in time to perform the Trail Making Test-A (median [IQR], 31.3 [27.0, 36.3] to 29.0 [19.4, 38.2] seconds, p = 0.02), however there was no difference compared to placebo (p = 0.29). After 12 months of treatment, there was a significant increase in resting pulsatility index of the MCA in the placebo group, but there were no statistical differences between groups (p = 0.71). NaHCO3 treatment resulted in a significant decrease in baseline mean blood flow velocity of the MCA (p = 0.03), but there was no difference from placebo (p = 0.11). Conclusions Although there were trends supporting a role for sodium bicarbonate in having an effect on cognitive function, this was not significant in this underpowered study. A larger study is recommended. Trial registration Clinicaltrials.gov (NCT04600323) on 10/19/2020.